Modern poultry-keeping flourishes in African villages - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Some African countries have forbidden the import of frozen European chickens, and this could trigger the revival of a modernized local poultry industry. But the poultry fanners who wish to take advantage of this will have to become more familiar...